Understanding innovation in education: A service co-production perspective - Luis Rubalcaba-Bermejo (Economies, 2022)
Innovation in education has been heavily focused on pedagogical, technological, or regulatory elements, while service innovation relates to other elements involving interpersonal and community co-production too. This paper provides a conceptual framework to understand innovation in education from a service economic perspective. This is done by bridging two rather disconnected research areas: service innovation and education innovation. The results indicate that (i) the characteristics of education as a service (such as interactive co-production) should be taken into account to better understand how innovations are created and implemented; (ii) innovation modes in education can be aligned with service innovation modes, mainly when a public service logic is adopted; (iii) the tension existing in service innovation between customization and standardization is replicated in the education sector; and (iv) multiagent frameworks in service innovation are particularly visible in innovative learning communities. Managerial and policy implications should be guided by service-friendly principles such as freedom, autonomy, and subsidiarity.
Keywords: 330; co-production; education; innovation; services